2017
DOI: 10.1016/j.cobme.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep tissue imaging with multiphoton fluorescence microscopy

Abstract: We present a review of imaging deep-tissue structures with multiphoton microscopy. We examine the effects of light scattering and absorption due to the optical properties of biological sample and identify 1,300 nm and 1,700 nm as ideal excitation wavelengths. We summarize the availability of fluorophores for multiphoton microscopy as well as ultrafast laser sources to excite available fluorophores. Lastly, we discuss the applications of multiphoton microscopy for neuroscience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(88 citation statements)
references
References 51 publications
0
88
0
Order By: Relevance
“…We predict that the development of GPCR sensors absorbing in this wavelength range, that could for instance be engineered based on bacterial phytochromes (e.g., BphP1; Yao et al, 2016), will enable successful application of the probes with optoacoustic imaging, a scalable imaging modality capable of resolving whole-brain activity three-dimensionally at millisecond time scale and 100 µm resolution non-invasively (i.e., without the need for optical fiber or gradient index lense implantation) (Gottschalk et al, 2019). Another advantage of red/NIR FPs is that their photophysical properties are optimal for threephoton absorption (3PA) in the 1700 nm optical window (Horton et al, 2013;Deng et al, 2019), which is recently emerging as a superior technique for deep in vivo imaging (Horton et al, 2013;Miller et al, 2017). Due to the much reduced scattering and absorption, 3PA at these wavelengths is limited only by signalto-noise ratio (which depends on protein brightness) up to more than 3 mm depth (Horton et al, 2013), and structural imaging of neurons has already been demonstrated at a depth of 1.4 mm (Horton et al, 2013), reaching the subcortical region of the mouse brain.…”
Section: The Push Toward Red-shifted Wavelengthsmentioning
confidence: 99%
“…We predict that the development of GPCR sensors absorbing in this wavelength range, that could for instance be engineered based on bacterial phytochromes (e.g., BphP1; Yao et al, 2016), will enable successful application of the probes with optoacoustic imaging, a scalable imaging modality capable of resolving whole-brain activity three-dimensionally at millisecond time scale and 100 µm resolution non-invasively (i.e., without the need for optical fiber or gradient index lense implantation) (Gottschalk et al, 2019). Another advantage of red/NIR FPs is that their photophysical properties are optimal for threephoton absorption (3PA) in the 1700 nm optical window (Horton et al, 2013;Deng et al, 2019), which is recently emerging as a superior technique for deep in vivo imaging (Horton et al, 2013;Miller et al, 2017). Due to the much reduced scattering and absorption, 3PA at these wavelengths is limited only by signalto-noise ratio (which depends on protein brightness) up to more than 3 mm depth (Horton et al, 2013), and structural imaging of neurons has already been demonstrated at a depth of 1.4 mm (Horton et al, 2013), reaching the subcortical region of the mouse brain.…”
Section: The Push Toward Red-shifted Wavelengthsmentioning
confidence: 99%
“…The two-photon fluorescence signal is very specific to the excitation and emission wavelengths of fluorophores. More information about the fluorophores in the local environment in tissue sections and biopsies can be obtained from the dynamics of the fluorescence signal [27][28][29][30].…”
Section: Two-photon Fluorescence Microscopymentioning
confidence: 99%
“…The fraction of excitation light reaching the focal volume at a depth, z, can be approximated as exp[-(µ a (λ)+µ s (λ))z], where µ a (λ) and µ s (λ) are wavelength-dependent absorption and scattering coefficients. 37 This function reveals that there is an ideal biological imaging wavelength situated at 1,300 nm 23 where photo-attenuation is minimized in brain tissue (Fig. S6).…”
Section: Polymer Dot Excitability At Longer Wavelengths Extends Vascumentioning
confidence: 99%
“…Moreover, the ability to excite polymer dots at longer wavelengths allows us to approach an ideal biological imaging wavelength situated at 1,300 nm where absorption and tissue scattering events are minimized. 8,23 For instance, the photophysical advantages of longer wavelength excitation of PFPV (λ ex = 1,060 nm) coupled with the ytterbium-fiber laser's intrinsic pulse characteristics results in a 3.5-fold improvement in SBR, and an overall 50 µm gain in penetration depth in vivo. Multiphoton imaging of CNPPV-labeled vasculature using an OPA (λ ex = 1225 nm) increases SBR by ~8.2 fold (z = 700 µm), and extends imaging depth 450 µm further into the brain.…”
Section: Introductionmentioning
confidence: 99%